Inhibition of induced-hepatic cancer in vivo through IQGAP1-shRNA gene therapy and modulation of TRAIL-induced apoptosis pathway - Zoheir, Khairy M. A.; Abd-Rabou, Ahmed A.; Darwish, Ahmed M.; Abdelhafez, Mohamed A.; Mahrous, Karima F. (Frontiers in Oncology, 2022)
Liver cancer is the deadliest malignancy among common tumors. It is the top cause of cancer-related deaths in Egypt, and it is characterized by increasing occurrence among the population. The objective of this study was to determine the outcome of pre-treatment of IQGAP1-shRNA on an induced mouse hepatocellular carcinoma model and evaluate the potency of this IQGAP1-shRNA plasmid to prevent hepatic cancer as a new tool of cancer therapy. Therefore, we will use RNA interference technology to silence IQGAP1 oncogene to completely recover the chemically induced models for hepatic cancer by designing short RNAi specific for IQGAP1 gene in HCC cells in vivo. Mice were divided into three groups: the first negative control group (NC) was injected with saline, the second control group was injected with shRNA (shNC), the third positive control group was injected with diethylnitrosamine (DENAA), and the fourth group was treated with the IQGAP1-shRNA prior to its exposure to DENA. Results revealed that the treated group with IQGAP1-shRNA with DENA developed very few cases of hepatic cancer when compared with the positive control group. The positive control group exhibited significant increases in the liver function level as well as a decrease in serum albumin levels when compared to both the treated and the negative control groups. Levels of the serum α-fetoprotein, tumor necrosis factor-alpha, and interleukin-4 in DENA-treated mice were significantly ameliorated by IQGAP1-shRNA administration. Flow cytometer analyses have indicated that the silencing of IQGAP1 cannot significantly modulate DENA-induced apoptosis in blood cells. Moreover, the elevated mRNA expression levels of IQGAP1, IQGAP3, KRas, HRas, interleukin-8, nuclear factor kappa B, caspase-3, caspase-9 and Bcl-2, were significantly decreased by the IQGAP1-shRNA treatment. However, the IQGAP2, DR4, DR5, p53 and BAX genes were found to be significantly up-regulated. IQGAP1-shRNA modulated the DENA-induced histological changes in the mice liver which were represented by severe necrosis and hydropic degenerative changes. IQGAP1-shRNA was able to preserve hepatocyte integrity and the liver histological architecture through the regulation of the expression of IQGAPs, Ras, TRAILs, and IL-8 receptors, as well as of pro-apoptotic and anti-apoptotic genes.er.